Efficacy and MRI of rituximab and methotrexate treatment in a nude rat model of CNS lymphoma - Jahnke, Kristoph (Duke University Press, 2009)
To determine the efficacy of methotrexate and/or rituximab in a CNS lymphoma model and to evaluate MRI modalities for monitoring efficacy, we inoculated female athymic nude rats (rnu/rnu) intracerebrally with human MC116 B-lymphoma cells. Between days 16 and 26, rats were randomized to receive intravenous (IV) treatment with (1) saline (controls, n = 15), (2) methotrexate 1,000 mg/m(2) (n = 6), (3) rituximab 375 mg/m(2) (n = 6), or (4) rituximab plus methotrexate (n = 6). T2/fluid-attenuated inversion recovery (FLAIR) and gadolinium contrast-enhanced T1 MRI sequences were performed prior to and 1 week after treatment. IV rituximab gave an objective tumor response in four of six animals (>50% reduction in tumor volume comparing pre- and posttreatment T2/FLAIR MRI) and resulted in stable disease (50%–125% of baseline) in another animal. The percent change in tumor volume on T2/FLAIR images was significantly different in the control versus rituximab group (p = 0.0051). IV methotrexate slowed tumor growth, compared to controls, but only one of six animals had an objective response. In untreated controls, tumor histological volumes correlated well with T2/FLAIR or contrast-enhanced T1 images (r = 0.877). In the treatment groups, T2/FLAIR correlation was good, but the gadolinium-enhanced T1 MRI was not significantly correlated with histology (r = 0.19). The MC116 CNS lymphoma model seems valuable for preclinical testing of efficacy and toxicity of treatment regimens. IV rituximab was highly effective, but methotrexate was only minimally effective. T2/FLAIR was superior to contrast-enhanced T1 for monitoring efficacy.